Explosive welding of aluminium to stainless steel using carbon steel and niobium interlayers - Carvalho, Gustavo (2020)
This work aimed to study aluminium to stainless steel explosive welds produced using two different interlayers: carbon steel and niobium. The use of each interlayer was analysed and compared microstructurally and mechanically using many characterisation techniques. The final joints using both interlayers presented favourable interfacial microstructure: waves on both interfaces. However, the joint using the carbon steel interlayer showed the best mechanical properties compared to the joints using the niobium interlayer. All interfaces found on both welds were wavy. However, depending on the metallic alloy combination, the shape of the wave is completely different. The results suggest that the shape of the waves is influenced by the shock impedance mismatch of the materials being welded. The impedance mismatch parameter (IMP) developed for explosive welding in this work proved to be a compelling method to order metallic combinations in a single axis to estimate the tendency to form typical or curled waves. Typical symmetrical waves tend to develop less quantity of IMCs than curled waves. However, the mechanical tests performed did not detect differences that could have been caused by this difference.